2022
DOI: 10.1038/s41416-022-01894-4
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I poison-triggered immune gene activation is markedly reduced in human small-cell lung cancers by impairment of the cGAS/STING pathway

Abstract: Background Current immunotherapy strategies have contrasting clinical results in human lung cancer patients as small-cell lung cancers (SCLC) often show features of immunological cold tumours. Topoisomerase 1 (TOP1) poisons are effective antitumor drugs with good efficacy against lung cancers. Methods We used molecular, genetic and bioinformatic approaches to determine the mechanism of micronuclei formation induced by two TOP1 poisons in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Likely, because TOP1i have significant immune modulatory effects (46)(47)(48)(49), future studies in immunocompetent mice may uncover aspects of long-acting IT delivery of the agents that better reflect expectations in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, because TOP1i have significant immune modulatory effects (46)(47)(48)(49), future studies in immunocompetent mice may uncover aspects of long-acting IT delivery of the agents that better reflect expectations in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that triple therapy further activated cGAS/STING signaling, increased CD8 + T cell proliferation and enhanced the immune memory activation that facilitated tumor regression and durable control. A previous report demonstrates that STING downregulation is generally observed in human lung cancer subtypes, including small-cell lung cancer, large-cell neuroendocrine lung cancer, LUAD and LUSC, in comparison to normal lung tissues [ 46 ]. To further confirm the effect of STING expression on patient survival, we analyzed TCGA dataset of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ] ATR and topoisomerase 1 (TOP1) inhibitor activates the STING pathway by micronuclei. [ 63 ] RNA polymerase I (POL I) CX‐5461 is one of the most promising POL I inhibitors being studied at present. Treatment with CX‐5461 can induce rapid accumulation of cytosolic DNA, leading to the up‐regulated transcription of STING.…”
Section: Sting Agonistsmentioning
confidence: 99%